The Link Between Clinically Validated Patient Safety Indicators and Clinical Outcomes. (November 2017) - Gray, Darrell M.; Hefner, Jennifer L.; Nguyen, Michelle C.; Eiferman, Daniel; Moffatt-Bruce, Susan D.
There is a paucity of evidence on the association between clinically validated Patient Safety Indicators (PSIs) and inpatient length of stay, mortality, and 30-day unplanned readmission. The authors perform a retrospective analysis of patient discharges from an academic medical center comprising 6 hospitals from July 2012 to June 2014. Multivariable regression models are used to assess the relationship between length of stay, mortality, and 30-day unplanned readmission and the presence of a clinically validated PSI. Cases flagged with a clinically validated PSI are associated with a statistically greater length of stay, 30-day unplanned readmission, and mortality as compared to cases without a PSI. This study demonstrates a strong association between clinically validated PSIs and patient outcomes. The findings have important implications in policy and practice as health care reform dictates improvement in the experience of care, health of populations, and per capita costs.